INFLUENCE OF SOWING DATE AND CLIMATE CONDITIONS ON THE PHENOLOGICAL PHASES OF DIFFERENT MAIZE HYBRIDS - Stojiljkovic, Jelena; Rajičić, Vera; Šević, Biljana; Tupajić, Ivan; Cvikić, Dejan; Jovanović, Darko; Biberdžić, Milan (Journal of Agricultural Sciences (Belgrade), 2025)
The experiment was set up during 2016/2017 in the area of ​​Leskovac, on alluvium-type land. For research purposes, the duration of certain phenological phases, the entire vegetation period of 6 corn hybrids, and three FAO ripening groups (400-600), were monitored. The research aims to determine the duration of individual phenological phases and the entire vegetation based on the number of days, the sum of the total, and the sum of the effective temperatures, and to recommend suitable hybrids for the investigated area. Observed by years and sowing dates, the difference in vegetation length between the hybrid with the longest and the hybrid with the shortest vegetation period was 38 days, the difference in SUT is 414.7 °C, and the difference in SET is 240.0 °C. On average for two years, the lowest sum of effective temperatures of 1158.8 °C was recorded in the hybrid FAO group 400 ZP 434, and the highest at 1398.9 °C in the hybrid FAO group 600, NS 6030. Depending on the temperature conditions, the year in the first sowing period of individual phases was shortened with increasing temperature. The onset of periods with lower air temperatures and the length of the phenological phases lasted longer. The method of the sum of effective temperatures proved to be the most reliable method for determining the vegetation length of the corn hybrids examined.
Keywords: maize, length of vegetation, number of days, total air temperature, effective temperature.